Le molte domande sollevate dal duplice concetto di “Elemento” - Scerri, Eric R.; Stoccoro, Sergio (Chimica nella Scuola, 2023)
This contribution takes up some problems exposed in the first chapter of the book “What is a Chemical Element?”, edited by Eric Scerri and Elena Ghibaudi, and published in 2020 by the Oxford University Press. It concerns a series of still open questions relating to chemical elements starting from the double meaning of the term “element”, which goes back to Lavoisier who identified the element with the simple substance and Mendeleev who considered the element as something present in simple substances and compounds but not detectable by our senses. These two meanings were later highlighted by Paneth in his double definition of simple substance and basic substance respectively. Paneth argued that these two meanings must remain separate if the fundamental principle of chemistry that elements persist in their compounds is to be affirmed. Unfortunately, IUPAC admits the double definition of element, thus fostering conceptual confusion between simple substance and element, which must necessarily be recognized a formal character expressed by its symbol and atomic number (which replaced Mendeleev's atomic weight after the discovery of isotopes). Chemists know how handle these double meanings of element, but this is not the case for students who encounter difficulties. We sincerely hope that these may help readers to better understand this concept, also considering that this problem is usually overlooked in textbooks who often speak of elements as simple substances with all their macroscopic properties, not present in their compounds, to the detriment of the more important formal meaning that underlie the periodic table.